Featherwork and Divine Chieftainship in Tonga - Herda, Phyllis; Lythberg, Billie (Waka Kuaka, 2014)
Pala tavake were sacred regalia, feather headdresses, reserved for the traditional sacred ruler of Tonga, the Tuâ€˜i Tonga. Recently a fanned featheredÂ headdress whose materials and construction are commensurate with 18th century Tongan objects was uncovered at Madridâ€™s Museo de AmÃ©rica. This paper considers the feather headdress located in Madrid, its probable historical context and connections â€“ both Tongan and Spanish. In addition we discuss the association of pala tavake with the Tuâ€˜i Tonga, the sacred ruler of Tonga, and the changing nature of the title in the late 18th century.